Metode High-Touch Berbasis Bimbingan Konseling Dalam Meningkatkan Motivasi Belajar Anak Usia Dini - Mahyatun, Baiq; Shofiyanti, Dessy; Purnomo, Dian (Universitas Muhammadiyah Sumatera Utara, 2021)
Teachers are not only required to be able to provide good teaching, provide good knowledge cognitively to students, so that students understand each material provided, but teachers should also be fun educators, educators who make students comfortable and motivated in learning. Even the teacher should also be the best model for students. Many cases occur, there are teachers whose students are not comfortable in class, teachers who always give corporal punishment, who are always angry with students. So this makes students' learning motivation to decrease, not only seen from their low learning outcomes, but also seen during learning activities at school, such as skipping class hours, often falling asleep, noisy in class and others. This paper discusses the application ofHigh-Touch, which is a counseling-based method, which can make learning fun, so that students become motivated in learning as; various efforts that can be done by the teacher, namely; 1). Generating student motivation by providing interesting learning methods. 2). Create a pleasant atmosphere in learning. 3). Using a variety of interesting presentation methods. 4). Give reasonable praise for each student's success. 5). Comment on student work. 6) Create competition and cooperation